A thermo-mechanically coupled finite strain model for phase-transitioning austenitic steels in ambient to cryogenic temperature range. (December 2019) - Kothari, Mrityunjay; Niu, Sijun; Srivastava, Vikas
Abstract: We present a finite-strain thermo-mechanically coupled continuum theory to model the material response of phase transitioning (metastable) austenitic steels from ambient (room) to cryogenic temperature. We applied our model to 316L stainless steel which shows plastic strain driven transformation from FCC austenite to BCC martensite phase at temperatures below room temperature and calibrated the model parameters using uniaxial tension tests at room and cryogenic temperatures. The constitutive model is able to successfully model the observed second strain-hardening behavior at cryogenic temperature due to formation of harder martensite at large strains. We implemented our coupled thermo-mechanical-phase transition model in the finite element program Abaqus by writing a user material subroutine and validated the model by conducting finite element based tension and compression simulations for a room temperature formed corrugated pipe. Comparisons of mechanical response between our simulation predictions and full-scale tests for the corrugated pipe at both room and cryogenic temperature show good accuracy of our model. We also conducted simulations to investigate the austenite-martensite phase transition near a notch tip in a flat plate geometry.